The Relationship Between Interest and Citizen Participation in Learning Computer Skills at PKBM Biba Course West Pasaman - Ayu Lestari; Syur'aini Syur'aini (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
ABSTRACTThis research aims to find out the relationship between interest and the participan of learning residents in taking computer skills at the PKBM Biba Course, west Pasanan. This research uses analysis techniques based on the percentage formula and Product Moment correlation formula. The result of this research are that people’s interest in learning computer skills at PKBM Biba Course West Pasaman was categorized as low, this was because respondents predominantly chose alternative answers with a score of two. There is a significant relationship between interest and student participation in taking computer skills at the PKBM Biba Course West Pasaman. Keywords: Interest, participation, Computer Skills, PKBM Biba Course